Tafsir Al-Qur’an di Media Sosial (Penafsiran Surah Al-Humazah dalam Youtube “Habib dan Cing”) - Nafiza, Azka Zahro; Muttaqin, Zaenal (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article discusses the interpretation of the Qur’an by Habib Husein Ja’far on “Habib dan Cing” YouTube channel. The development of digital media creates a new opportunity of Islamic preachers to use the digital media to widen their audiences. Habib Husein and Abdel Achrian employ the “Habib dan Cing” channel to perform da’wa which contains the interpretation of the Qur’anic verses (tafsir). This paper focuses specifically on the interpretation of the Qur’an sura al-Humaza (the traducer). This research finds that Habib Husein’s Qur’anic interpretation can be characterized as social tafsir which is delivered with millennial style, full of jokes and laughs, which makes the tafsir is easily understood by the public. Among influential factors that shape his tafsir are its rooted references to the classical as well as modern tafsir, his relevant educational background, and its connection to the contemporary Indonesian society.